Species delimitation of common reef corals in the genus Pocillopora using nucleotide sequence phylogenies, population genetics and symbiosis ecology - PINZÓN, JORGE H.; LaJEUNESSE, TODD C. (Molecular ecology, 2011)
Stony corals in the genus Pocillopora are among the most common and widely distributed of Indo‐Pacific corals and, as such, are often the subject of physiological and ecological research. In the far Tropical Eastern Pacific (TEP), they are major constituents of shallow coral communities, exhibiting considerable variability in colony shape and branch morphology and marked differences in response to thermal stress. Numerous intermediates occur between morphospecies that may relate to extensive hybridization. The diversity of the Pocillopora genus in the TEP was analysed genetically using nuclear ribosomal (ITS2) and mitochondrial (ORF) sequences, and population genetic markers (seven microsatellite loci). The resident dinoflagellate endosymbiont (Symbiodinium sp.) in each sample was also characterized using sequences of the internal transcribed spacer 2 (ITS2) rDNA and the noncoding region of the chloroplast psbA minicircle. From these analyses, three symbiotically distinct, reproductively isolated, nonhybridizing, evolutionarily divergent animal lineages were identified. Designated types 1, 2 and 3, these groupings were incongruent with traditional morphospecies classification. Type 1 was abundant and widespread throughout the TEP; type 2 was restricted to the Clipperton Atoll; and type 3 was found only in Panama and the Galapagos Islands. Each type harboured a different Symbiodinium‘species lineage’ in Clade C, and only type 1 associated with the ‘stress‐tolerant’Symbiodinium glynni (D1). The accurate delineation of species and implementation of a proper taxonomy may profoundly improve our assessment of Pocillopora’s reproductive biology, biogeographic distributions, and resilience to climate warming, information that must be considered when planning for the conservation of reef corals.